Bigu-Style Fasting Affects Metabolic Health by Modulating Taurine, Glucose, and Cholesterol Homeostasis in Healthy Young Adults. Issue 8 (12th May 2021) - Tang, Lixu; Li, Lili; Bu, Lihong; Guo, Shaoying; He, Yuan; Liu, Liying; Xing, Yangqi; Lou, Fangxiao; Zhang, Fengcheng; Wang, Shun; Lv, Jian; Guo, Ningning; et al.
ABSTRACT: Background: Dynamic orchestration of metabolic pathways during continuous fasting remains unclear. Objective: We investigated the physiological effects of Bigu-style fasting and underlying metabolic reprogramming in healthy adults. Methods: We conducted a 5-d Bigu trial in 43 healthy subjects [age 23.2 ± 2.4 y; BMI (in kg/m 2 ) 22.52 ± 1.79]. Physiological indicators and body composition were monitored daily during fasting day 1 (F1D) to F5D and after 10-d refeeding postfasting (R10D) and R30D. Blood samples were collected in the morning. Risk factors associated with inflammation, aging, cardiovascular diseases, malnutrition, and organ dysfunction were evaluated by biochemical measurements. Untargeted plasma metabolomics and gut microbial profiling were performed using plasma and fecal samples. Data were analyzed by repeated measures ANOVA with Greenhouse–Geisser correction. Correlation analyses for metabolite modules and taurine were analyzed by Spearman's rank and Pearson tests, respectively. Results: Heart rate was accelerated throughout the fasting period. Risk factors associated with inflammation and cardiovascular diseases were significantly lowered during or after Bigu ( P < 0.05). Body composition measurement detected an overconsumption of fat starting from F3D till 1 mo after refeeding. Metabolomics unveiled a coupling between gluconeogenesis and cholesterol biosynthesis beyond F3D. Plasma taurine significantly increased at F3D by 31%–46% followed by a reduction to basal level at F5D ( P < 0.001), a pattern inversely correlated with changes in glucose and de novo synthesized cholesterol ( r = −0.407 and −0.296, respectively; P < 0.001). Gut microbial profiling showed an enrichment of taurine-utilizing bacteria at F5D, which was completely recovered at R10D. Conclusions: Our data demonstrate that 5-d Bigu is potentially beneficial to health in young adults. A starvation threshold of 3-d fasting is necessary for maintaining glucose and cholesterol homeostasis via a taurine–microbiota regulatory loop. Our findings provide novel insights into the physiological and metabolic responses of the human body to continuous Bigu-style fasting. This trial was registered at http://www.chictr.org.cn as ChiCTR1900022917.